FACILITIES FOR RESTORATION OF MONORAIL OF MECHANIZATION OF A WING OF AIRCRAFTS - Kralya, Vitaliy; Khimko Аndrey; Borodiy, Victor; Yakobchuk, Alexander (Proceedings of National Aviation University (archive), 2006)
The adaptations on removal of a defective layer and grinding of monorail of extension - retraction of flaps and slats of aircrafts are developed. Their application will allow essentially to lower time spent on restoration of a monorail, and will raise quality of processing of a detail at repair.